2018
DOI: 10.1073/pnas.1800727115
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila model of myosin myopathy rescued by overexpression of a TRIM-protein family member

Abstract: Myosin is a molecular motor indispensable for body movement and heart contractility. Apart from pure cardiomyopathy, mutations in encoding slow/β-cardiac myosin heavy chain also cause skeletal muscle disease with or without cardiac involvement. Mutations within the α-helical rod domain of are mainly associated with Laing distal myopathy. To investigate the mechanisms underlying the pathology of the recurrent causative mutation (K1729del), we have developed a model of Laing distal myopathy by genomic engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 41 publications
(63 reference statements)
3
21
0
Order By: Relevance
“…In addition to the stoichiometric argument, the energetic argument to be able to draw on a local pool of protein, rather than solely relying on newly synthesized protein adds tremendous flexibility during states of metabolic stress when transcription and translation may be affected. Furthermore, augmentation of the protein quality control machinery (both proteasomal as well as the autophagylysosomal pathway) is associated with benefits and sarcomere recovery in a variety of heart failure models associated with sarcomere dysfunction even in the absence of correction of the primary genetic abnormality (such as mutations in MYH7, desmin, and CryAB) (Li et al, 2011;Pattison et al, 2011;Ranek et al, 2013;Gupta et al, 2014;McLendon et al, 2014;Cabet et al, 2015;Su et al, 2015;Dahl-Halvarsson et al, 2018;. Thus, various elements of the "sarcostat" are in dynamic equilibrium, whereby perturbations in one element (either genetic or environmental) induce structural and functional abnormalities, and therapeutic targeting of this inciting stimulus or another balancing node can restore homeostasis.…”
Section: Sarcostat: a Proposed Framework To Understand Sarcomeric Pqcmentioning
confidence: 99%
“…In addition to the stoichiometric argument, the energetic argument to be able to draw on a local pool of protein, rather than solely relying on newly synthesized protein adds tremendous flexibility during states of metabolic stress when transcription and translation may be affected. Furthermore, augmentation of the protein quality control machinery (both proteasomal as well as the autophagylysosomal pathway) is associated with benefits and sarcomere recovery in a variety of heart failure models associated with sarcomere dysfunction even in the absence of correction of the primary genetic abnormality (such as mutations in MYH7, desmin, and CryAB) (Li et al, 2011;Pattison et al, 2011;Ranek et al, 2013;Gupta et al, 2014;McLendon et al, 2014;Cabet et al, 2015;Su et al, 2015;Dahl-Halvarsson et al, 2018;. Thus, various elements of the "sarcostat" are in dynamic equilibrium, whereby perturbations in one element (either genetic or environmental) induce structural and functional abnormalities, and therapeutic targeting of this inciting stimulus or another balancing node can restore homeostasis.…”
Section: Sarcostat: a Proposed Framework To Understand Sarcomeric Pqcmentioning
confidence: 99%
“…A study has shown that the formation of large aggregates in muscles similar to those seen in human patients with ZASP mutations is caused by an imbalance in the levels of Zasp isoforms [ 246 ]. Dahl-Halvarsson et al showed that the overexpression of the Thin protein, a homolog of the human TRIM family of proteins that is implicated in maintaining sarcomeric integrity, could alleviate LDM-like phenotypes [ 305 ].…”
Section: The Maintenance Of Muscle Homeostasismentioning
confidence: 99%
“…Finally, there are currently no models for MYH7, TTN or ACTA1 mutations, which cause a subset of MmD with cardiac involvement (Chauveau et al, 2014;Cullup et al, 2012;Kaindl, 2004). However, Drosophila with Laing-distal-myopathy-associated L1729del myh7 mutations develop myofibril disruption, cores and mitochondrial abnormalities, further blurring the genotypephenotype boundaries (Dahl-Halvarsson et al, 2018).…”
Section: Recessive Ryr1 Modelsmentioning
confidence: 99%